2021
DOI: 10.3390/vaccines9070768
|View full text |Cite
|
Sign up to set email alerts
|

Intranasal Administration of RBD Nanoparticles Confers Induction of Mucosal and Systemic Immunity against SARS-CoV-2

Abstract: Mucosal immunity plays a significant role in host defense against viruses in the respiratory tract. Because the upper respiratory airway is a primary site of SARS-CoV-2 entry, immunization at the mucosa via the intranasal route could potentially lead to induction of local sterilizing immunity that protects against SARS-CoV-2 infection. In this study, we evaluated the immunogenicity of a receptor-binding domain (RBD) of SARS-CoV-2 spike glycoprotein loaded into N,N,N-trimethyl chitosan nanoparticles (RBD-TMC NP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 49 publications
0
28
0
1
Order By: Relevance
“…Not only did this mode of delivery activates local mucosal responses, but it also activated the immune system’s systemic component. 72 …”
Section: Intranasal Covid-19 Vaccinesmentioning
confidence: 99%
“…Not only did this mode of delivery activates local mucosal responses, but it also activated the immune system’s systemic component. 72 …”
Section: Intranasal Covid-19 Vaccinesmentioning
confidence: 99%
“…The purified protein was evaluated by immunoblotting analysis using mouse anti-His (C-term) antibodies (Invitrogen, Carlsbad, CA, USA) and rabbit anti-SARS-CoV-2 receptor-binding domain (RBD) polyclonal antibodies (Sino Biological, Beijing, China). The SARS-CoV-2 RBD protein used throughout the study was prepared in-house as previously described [22].…”
Section: Production Of Recombinant Sars-cov-2 Spike Proteinmentioning
confidence: 99%
“…The optical density (OD) at 450 nm was read using an ELISA reader. The cut-off endpoint titers (EPT) of antigen-specific antibodies were shown as the reciprocal of the highest dilution of samples with an OD value equal to or more than three times the OD value of blank controls [22].…”
Section: Antigen-specific Antibodies Detected Using the Elisa Assaymentioning
confidence: 99%
See 1 more Smart Citation
“…Chitosan (CS), with positive charges, is a natural mucoadhesive material with cGAS-STING-dependent adjuvanticity [22][23][24]. Many studies have indicated that chitosan is an effective mucosal vaccine adjuvant for many antigens [25][26][27], such as ovalbumin protein (OVA) [25] and receptor-binding domain (RBD) of SARS-CoV-2 spike protein [27]. Additionally, chitosan can open intercellular tight junctions temporarily [28], which is beneficial for drugs to pass through the intercellular space, thus improving tissue penetration and amplifying humoral and cellular immunity.…”
Section: Introductionmentioning
confidence: 99%